Module Development Based on Communicative Approach to Indonesian Language Learning to Improve Speaking Skills of Elementary School Students - Siti Habsari Pratiwi; Eva Faridah; Nurdin Bukit; Edy Surya (Pedagogik Journal of Islamic Elementary School, 2023)
This research aims to improve students' speaking skills. This research is research and development, using the Four D development model, which consists of the define, design, develop, disseminate stages. This research has reached the development stage. The research was carried out at MIN 3 Langsa. The subjects in the research were 25 class III students consisting of 13 female students and 12 male students. The object in the research ismodule based on a communicative approach to Indonesian language lessons. The collection techniques used are observation, tests and questionnaires. Based on the results of validation by experts carried out on modules based on communicative approaches in Indonesian language lessons, the results of validation by language experts are in percentages 94.10% is categorized as very feasible, material expert validation with a percentage of 80.00% is categorized as feasible, and media expert validation results with a percentage 90.70% categorized as very feasible, and validated by media experts with percentages 93.45% categorized as very feasible. Based on this description, it is concluded thata module based on a communicative approach to Indonesian language lessons is suitable for use at MIN 3 Langsa. The results of the pretest were 4 students who completed and 21 students who did not complete with a percentage of 46%. Meanwhile, 23 students completed the posttest and 2 students did not complete the test with a percentage of 70%. Based on this explanation, it was concluded that using a communicative approach based module in Indonesian language lessons was said to be effective for class III students at MIN 3 Langsa. Based on the results and discussion in this research, it is known that the communicative approach based module in Indonesian language lessons is said to be very feasible and effective for use with class III students at MIN 3 Langsa.